Chemical and structural characterization of V2O5/TiO2 catalysts - Rodella, C. B.; Nascente, PAP; Mastelaro, V. R.; Zucchi, M. R.; Franco, RWA; Magon, C. J.; Donoso, P.; Florentino, A. O. (American Institute of Physics (AIP), 2001)
A series of V2O5/TiO2 samples was synthesized by sol-gel and impregnation methods with different contents of vanadia. These samples were characterized by x-ray diffraction (XRD), Raman spectroscopy, x-ray photoelectron spectroscopy (XPS), and electronic paramagnetic resonance (EPR). XRD detected rutile as the predominant phase for pure TiO2 prepared by the sol-gel method. The structure changed to anatase when the vanadia loading was increased. Also, anatase was the predominant phase for samples obtained by the impregnation method. Raman measurements identified two species of surface vanadium: monomeric vanadyl (V4+) and polymeric vanadates (V5+). XPS results indicated that Ti ions were in octahedral position surrounded by oxygen ions. The V/Ti atomic ratios showed that V ions were highly dispersed on the vanadia/titania surface obtained by the sol-gel method. EPR analysis detected three V4+ ion types: two of them were located in axially symmetric sites substituting for Ti4+ ions in the rutile structure, and the third one was characterized by magnetically interacting V4+ ions in the form of pairs or clusters. A partial oxidation of V4+ to V5+ was evident from EPR analysis for materials with higher concentrations of vanadium. (C) 2001 American Vacuum Society.